(Re)affirming identities: implementing a play-based approach to learning in the early years of schooling. Issue 1 (2nd January 2018) - Nolan, Andrea; Paatsch, Louise
ABSTRACT: Learning through play has traditionally been a central tenet in early childhood education, however, in recent times primary schools have begun to consider the benefits of introducing a play-based approach into early years classrooms to support young children's learning, especially in the areas of language and literacy. This study focuses on the introduction of a play-based approach to a Foundation classroom (first year of formal schooling) in one Catholic primary school in Victoria, Australia. Taking a qualitative approach, drawing on interpretivist theory, data collection methods included group interviews with two Foundation teachers and their Early Years Coordinator at different points during the year, and two classroom observation sessions. This paper considers some of the challenges these teachers experienced and how they interpret and make sense of their work and the consequences this has for their identities as teachers. The data highlight tensions for these teachers that relate to issues of accountability and legitimisation.